German Learning Media Application in Class X Senior High School - Insenalia Sampe Roly Hutagalung (EDUKATIF : JURNAL ILMU PENDIDIKAN, 2022)
The purpose of this study was to describe the use of learning media in learning German in class X SMA Nommensen Pematangsiantar Campus. The data collection was carried out by the methods of observation, interviews, and documentation. The research data will be analyzed using a qualitative descriptive method. The results showed that (1) the use of German language learning media in class X SMA Nommensen Pematangsiantar Campus that had been implemented such as visual media ( PowerPoint, laptop ), silent projection media ( LCD projector), simple visual media (real objects in the classroom ). , whiteboards, picture cards, letter cards, textbooks), audio media ( speakers ). (2) The obstacles faced by teachers in the use of media are derived from media selection techniques and student characteristics. The teacher's solution to overcoming obstacles to the use of learning media is to adjust the learning media to the material and adjust the learning media used to the conditions of the participants educate.